2020
DOI: 10.3390/jcm9092817
|View full text |Cite
|
Sign up to set email alerts
|

Photo and Plasma Activation of Dental Implant Titanium Surfaces. A Systematic Review with Meta-Analysis of Pre-Clinical Studies

Abstract: Background: Ultraviolet (UV) and non-thermal plasma functionalization are surface treatment modalities that seem able to improve osseointegration. The aim of this systematic review and meta-analysis is to assess the effect of the two methods and possible differences. Materials and Methods: The systematic research of pre-clinical animal studies was conducted up to May 2020 in the databases PubMed/Medline, Scopus and the Cochrane Lybrary. A meta-analysis was performed by using the DerSimonian–Laird estimator in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
39
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 61 publications
0
39
0
Order By: Relevance
“…Focusing on the abutment surface, a “combed” surface (UTM) seems to improve the soft tissue healing pattern compared with MAC. Recently published systematic reviews (Canullo, Genova, et al., 2020; Canullo, Menini, et al., 2020; Pesce et al., 2020) confirmed that short‐term data (<6 months) suggested an enhanced connective fiber attachment next to titanium abutments with a modified surface as well as a similar inflammatory response relative to machine surface.…”
Section: Discussionmentioning
confidence: 90%
“…Focusing on the abutment surface, a “combed” surface (UTM) seems to improve the soft tissue healing pattern compared with MAC. Recently published systematic reviews (Canullo, Genova, et al., 2020; Canullo, Menini, et al., 2020; Pesce et al., 2020) confirmed that short‐term data (<6 months) suggested an enhanced connective fiber attachment next to titanium abutments with a modified surface as well as a similar inflammatory response relative to machine surface.…”
Section: Discussionmentioning
confidence: 90%
“…Moreover, preclinical animal studies with a focus on argon plasma treatment revealed enhanced boneto-implant contact (BIC) after functionalization of implant surfaces [33]. A recent meta-analysis came to conclusion that plasma treatment using argon may present an effective method for improving osseointegration [34]. Other investigations have also demonstrated enhanced osseointegration through ambient air-generated CAP for titanium surfaces and calcium-phosphate-coated implants [35].…”
Section: Discussionmentioning
confidence: 99%
“…Other animal experiments studied the osteoconductivity of different surfaces at marginal defects [ 39 , 40 , 41 ] showing that the surface modification affects osteoconductivity. It was also shown that a UV treatment of the implant surface improved osseointegration of implants [ 42 ]. Additionally, a treatment of titanium implants with argon plasma induces surface modifications, resulting in increased wettability, protein absorption, and cell adhesion [ 43 ], as shown by a higher number of adhered cells [ 44 , 45 , 46 ].…”
Section: Introductionmentioning
confidence: 99%